Transformasi Fiqih Minoritas ke Fiqih Mayoritas: Studi Etika Pergaulan dengan Tetangga Non-Muslim dalam Konteks Indonesia - Abid Nurhuda; Ali Anhar Syi’bul Huda; Ahmad Hadi Pranoto; Siti Rohmah; Dena Sri Anugrah (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2025)
This study examines the transformation of minority fiqh to majority fiqh with a focus on the ethics of interacting with non-Muslim neighbors in the Indonesian context. Minority fiqh (fiqh al-aqalliyyat) has traditionally emphasized flexibility, tolerance, and maslahah (public interest) for Muslims living as a minority. However, in the Indonesian context, where Muslims are the majority, a new paradigm is needed: majority fiqh that is not trapped in exclusivism, but rather oriented towards inclusiveness and social responsibility. Through a critical-transformative literary approach, this study examines normative texts (the Qur'an, Hadith, classical and contemporary fiqh books) as well as secondary literature (social research, academic works on Islam Nusantara, and theories of coexistence). The analysis is conducted using normative hermeneutics, a historical-sociological approach, and transformative synthesis. The results show that neighborly ethics such as mutual assistance, maintaining collective security, and sharing in social activities are the most tangible practical space for the implementation of inclusive majority fiqh. This study concludes that the transformation of fiqh from minority to majority is a shift from protective fiqh to collaborative fiqh. Majority fiqh is not merely about preserving Islamic identity, but also serves as a social force that strengthens interfaith harmony in a pluralistic society. Thus, majority fiqh can become the foundation for the development of applicable national fiqh in Indonesia.